1985
DOI: 10.1152/ajpendo.1985.249.5.e447
|View full text |Cite
|
Sign up to set email alerts
|

Direct effect of insulin on albumin gene expression in primary cultures of rat hepatocytes

Abstract: The purpose of this study was to identify a cell culture system in which the role of insulin in regulating albumin gene expression could be investigated. The system selected was rat hepatocytes maintained in primary culture in a chemically defined, serum-free medium. Under control conditions albumin secretion was nearly the same as the rate recorded in vivo and in perfused liver and was reasonably well maintained during 8 days of culture. Deletion of insulin from the culture medium for 3-6 days resulted in 40-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 33 publications
2
25
1
2
Order By: Relevance
“…3). On the other hand, previous studies showed that albumin mRNA concentration and albumin synthesis are increased by insulin (35)(36)(37)(38). Therefore, the albumin improvement effect by dietary MCT may also be attributable to direct albumin mRNA expression through increased plasma insulin concentration.…”
Section: Discussionmentioning
confidence: 93%
“…3). On the other hand, previous studies showed that albumin mRNA concentration and albumin synthesis are increased by insulin (35)(36)(37)(38). Therefore, the albumin improvement effect by dietary MCT may also be attributable to direct albumin mRNA expression through increased plasma insulin concentration.…”
Section: Discussionmentioning
confidence: 93%
“…Posteriormente, se o período de privação se estende, ocorre uma redução no número de mRNA responsáveis pela síntese de albumina. Este mecanismo é uma resposta adaptativa, lenta, à falta de substratos, e não é rapidamente reversível 17 . A oferta de energia parece ter uma importância maior que a de proteína na produção fisiológica de albumina, o que é justificado pelos mecanismos compensatórios expostos anteriormente.…”
Section: Metabolismo Da Albuminaunclassified
“…In diabetes, the concentration of albumin in blood is decreased, and administration of insulin is required to prevent hypoalbuminemia (6,7). Early biochemical studies have shown that insulin stimulates albumin production in the liver by activating gene transcription (5)(6)(7)(8)(9)(10)(11)(12). However, the detailed pathway by which insulin exerts this effect has not been described.…”
mentioning
confidence: 99%